2013
DOI: 10.33549/physiolres.932438
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Metabolic Syndrome in Obese Czech Children: the Importance of Early Detection of Insulin Resistance Using Homeostatic Indexes HOMA-IR and QUICKI

Abstract: Common alimentary obesity frequently occurs on a polygenic basis as a typical lifestyle disorder in the developed countries. It is associated with characteristic complex metabolic changes, which are the cornerstones for future metabolic syndrome development. The aims of our study were 1) to determine the incidence of metabolic syndrome (based on the diagnostic criteria defined by the International Diabetes Federation for children and adolescents) in Czech obese children, 2) to evaluate the incidence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 28 publications
2
9
1
Order By: Relevance
“…Next to establishing utility of HOMA-TG index, we observed QUICKI and G/I ratio to be least effective with lowest AUC in ROC curve analysis. This data contrasts to some of the previous finding as demonstrated by Pastucha et al [24] where the researchers identified insulin resistance in 86% of children in comparison to 56% by HOMAIR. Similarly, Bahijri et al [25] who found over estimation of insulin resistance by using QUICKI equation than HOMAIR.…”
Section: Discussioncontrasting
confidence: 99%
“…Next to establishing utility of HOMA-TG index, we observed QUICKI and G/I ratio to be least effective with lowest AUC in ROC curve analysis. This data contrasts to some of the previous finding as demonstrated by Pastucha et al [24] where the researchers identified insulin resistance in 86% of children in comparison to 56% by HOMAIR. Similarly, Bahijri et al [25] who found over estimation of insulin resistance by using QUICKI equation than HOMAIR.…”
Section: Discussioncontrasting
confidence: 99%
“…Studies have been conducted in order to define the diagnostic criteria and cutoff points to determine IR using Homeostatic model assessment (HOMA)-IR, or fasting plasma insulin, although the first is controversial [ 18 ]. The hyperinsulinemic- euglycemic clamp, the gold standard for the diagnosis of IR, is not applicable in clinical practice due to its technical complexity, especially in the pediatric age group [ 9 19 20 21 22 23 24 25 ]. According to Sinaiko [ 13 ], the values of fasting glucose and plasma insulin are the only ones required to calculate HOMA-IR, which intends to demonstrate the correlation between pancreatic capability of insulin production and the capacity of maintaining adequate glucose.…”
Section: Introductionmentioning
confidence: 99%
“…The need for evidence-based treatment recommendations is a critical healthcare issue because obese children and adolescents are at risk for developing many co-morbidities observed in obese adults. This increase in weight, as well as the decrease in physical activity and cardiorespiratory fitness levels [ 6 ], are in direct proportion to an increasing prevalence of impaired glucose tolerance (IGT) [ 7 ], metabolic syndrome (MetS) [ 8 , 9 ], and type 2 diabetes (T2DM) [ 10 ]. Nevertheless, many data show lower rates in Europe compared to North American data [ 11 ].…”
Section: Introductionmentioning
confidence: 99%